Preserflo™-Baerveldt Hybrid Implant: A Novel Approach for Glaucoma Drainage Surgery - Mifsud, Adrian; Sanhueza, Enrique; Lim., Kin Sheng (Journal of Ophthalmology and Research, 2024)
Purpose: To investigate the efficacy and safety of a new technique connecting a Baerveldt glaucoma implant to a PreserfloTM micro-shunt. Design: Retrospective non-comparative consecutive case series. Methods: A retrospective consecutive case series analysing data collected from Electronic Patient Records at St Thomas’ Hospital. All procedures were performed by a single surgeon (KSL) between November 2021 and February 2023. The following data were collected: demographic variables, IOP, number of glaucoma medications, complications and glaucoma subtype. Results: Ten eyes underwent connection of the Baerveldt glaucoma plate to a Preserflo™ implant either as a primary combined procedure or as a secondary staged procedure. The mean age of our patients was 68.4 ± 10.9. The mean preoperative IOP was 25.6 ± 7.5 mmHg. The mean number of topical glaucoma medication preoperatively was 3.4 ± 0.7 with 4 patients also being on acetazolamide. All complications resolved without sequalae. One patient needed injection of viscoelastic at the slit lamp. At 6 months, the mean IOP was 11.7 ± 3.7 mmHg with a mean number of topical glaucoma medication of 0.7 ± 1.2, with 70% being off glaucoma medication. At 1 year, the mean IOP at 1 year was 11.7 ± 4.2 mmHg with a mean number of topical glaucoma medication of 1.1 ± 1.2, with 44% being on no glaucoma medications. Conclusions: This novel technique is a safe and effective way to use as a primary combined procedure in high-risk eyes where Preserflo™ is likely to fail. It can also be used as a secondary procedure to salvage a failed PreserfloTM.